Methods and Ways of Forming Creative Competence in Students - Mirzukurov Mirziyod Mirodil ugli (International Journal on Integrated Education, 2023)
In this article, the ways and methods of the formation and development of creative abilities of students during the educational process in general education schools are described in detail.